2021
DOI: 10.3389/fcimb.2021.595716
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Vaginal Microorganisms and Serum Metabolomics in Rats With Estrous Cycle Disorder Induced by Long-Term Heat Exposure Based on 16S rDNA Gene Sequencing and LC/MS-Based Metabolomics

Abstract: Long term heat exposure (HE) leads to estrous cycle disorder (ECD) in female rats and damages reproductive function. However, the regulation mechanism of vaginal microorganisms and serum metabolomics remains unclear. This study aimed to explore the effects of microbes on the vaginal secretions of rats with ECD and describe the serum metabolomics characteristics and their relationship with vaginal microorganisms. The alterations in the serum levels of neurotransmitters were used to verify the possible regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…Surprisingly, in this study, the relative abundance of Firmicutes decreased in the Heat group while the relative abundance of Actinobacteria and Proteobacteria increased ( Ceccarani et al, 2019 ). Corynebacterium , one of the dominant genera in rabbit vagina, increased its relative abundance in the Heat group, which is consistent with a previous study that demonstrated an increase in the abundance of Corynebacterium in rat vagina after heat-stress treatment ( An et al, 2021 ). It has been suggested that Fusobacterium is one of the most abundant genera in cows ( Santos et al, 2011 ; Jeon et al, 2015 ) and canines ( Lyman et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Surprisingly, in this study, the relative abundance of Firmicutes decreased in the Heat group while the relative abundance of Actinobacteria and Proteobacteria increased ( Ceccarani et al, 2019 ). Corynebacterium , one of the dominant genera in rabbit vagina, increased its relative abundance in the Heat group, which is consistent with a previous study that demonstrated an increase in the abundance of Corynebacterium in rat vagina after heat-stress treatment ( An et al, 2021 ). It has been suggested that Fusobacterium is one of the most abundant genera in cows ( Santos et al, 2011 ; Jeon et al, 2015 ) and canines ( Lyman et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have also confirmed that heat stress can disrupt ovarian signaling ( Dickson et al, 2018 ), impair estradiol synthesis of granulosa cells ( Li H. et al, 2017 ), and affect ovarian hormone secretion ( Sirotkin, 2010 ). Additionally, heat stress disturbs the ecological communities in the vagina ( An et al, 2021 ), potentially impacting the normal function of the female reproductive tract (FRT). In this study, no significant changes were observed in plasma E 2 and P 4 in the Heat group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a large number of studies have shown that metabolic changes and intestinal microbiota disorders were parallel during the disease progression ( 65 , 66 ). Dysbiosis of the gut microbiota was accompanied with the alteration of plasma metabolome in calves with DHD.…”
Section: Discussionmentioning
confidence: 99%
“…Sequencing libraries were generated with NEB Next ® Ultra™DNA Library Prep Kit (NEB, United States) following the manufacturer’s instruction. The library was then sequenced on an Illumina NovaSeq 6000 platform, and fragments with 250 bp paired-end reads were generated ( An et al, 2021 ). Fast length adjustment of short (FLASH) reads were applied to merge the paired-end reads from the original DNA fragments, which were assigned to each sample through the unique barcodes.…”
Section: Methodsmentioning
confidence: 99%